Fontes e doses de biofertilizantes nas culturas da soja e do milho - Ponce, Maria Clara Resende (2022)
Several studies indicate that the application of humic substances can provide numerous benefits to the soil-plant system, such as greater absorption of nutrients and greater plant development, resulting in productivity gains in several cultures. In this context, the objective of this work was to evaluate the growth attributes, nutritional aspects and yield, as well as the chemical attributes of the soil after harvest, as a function of the application of biofertilizers containing fulvic and humic acids in the sowing furrow, in the soybean and corn crops. The experiments were carried out simultaneously in the municipality of Paracatu, Minas Gerais, in a randomized block design, with four replications, in a 4 x 3 + 1 factorial structure. The first factor formed by four different sources of biofertilizers (identified as Biof. 1, Biof. 2, Biof. 3 and Biof. 4), the second factor attended by the use of three doses (2, 4 and 6 L ha-1), and the additional treatment as the absence of application of humic substances (control), totaling 13 treatments. In the experiments, different results were observed with the application of humic substances. Different results were observed between the sources and doses evaluated of biofertilizers containing humic substances. Having the appropriate dose varied according to the biofertilizer and the culture. For soybean, biofertilizers increased nutrient uptake by plants, and nutrient availability in the soil. No interference was observed in the variables of growth and crop yield. For the corn crop, the biofertilizers promoted an increase in plant growth, and affected the absorption of nutrients. Not interfering with corn crop yield and soil chemical characteristics.